Detention without trial necessary in proposed Anti-Terrorism Act: Legal expert - Daily Express, (KK) (Daily Express, 2014)
KUALA LUMPUR: A legal expert says it may be necessary to incorporate detention without trial in the proposed Anti Terrorism Act if the government is really serious about enacting fresh laws to fight terrorism in the country.